Critique of Iran's Development Plans in terms of financial sector and real sector communication - Seyyed Ehsan Khondouzi; Mohsen Moghiseh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The relationship between the financial and real sector has always been a major concern in economic development programs and has been the topic of the theoretical controversy. The analysis of the text of the First Development Plan's sixth Development Law document shows that the gradual approach to financial guidance in favor of the real-life objectives is to replace financial liberalization. Indeed, in spite of the fact that Iran's financial support base is in the past few decades, we have not had a successful experience in supporting the production sector by banks and the financial sector, and even one cannot say that it was a coherent policy-oriented model. This article, by introducing some successful global experiences of the Credit Leadership Model (Japan, Germany, China, South Korea), attempts, based on the theoretical foundations of individuals such as Werner, in the form of a review of development plans, an alternative approach to support Production by the financial sector in which the government simultaneously plays a role in these financially-makers in the compilation of competitive producers in the real sector and in the management of bank credit.